High‐Performance Lithium‐Ion Capacitors Based on Porosity‐Regulated Zirconium Metal−Organic Frameworks. Issue 22 (3rd December 2020) - Yan, Wen; Su, Jian; Yang, Zhi‐Mei; Lv, Sen; Jin, Zhong; Zuo, Jing‐Lin
Abstract: Comprised of a battery anode and a supercapacitor cathode, hybrid lithium‐ion capacitors (HLICs) are found to be an effective solution to realize both high power density and high energy density at the same time. Organic–inorganic hybrid materials with well‐organized framework guided by the reticular chemistry are one of the promising anode materials for HLICs because of rich active sites and ordered porosity. Herein, metal−organic framework consisting of Zr 4+ metal ions and tetrathiafulvalene‐based ligands (Zr‐MOF) is proposed as the pseudocapacitive anode of HLICs. The Zr‐MOF possesses high stability, high crystallinity, and multiple meso‐microporous channels favorable for ion transport. The as‐prepared Zr‐MOF||activated carbon HLICs present high energy density (122.5 Wh kg −1 ), high power density (12.5 kW kg −1 ), and stable cycling performance (86% capacity retention after 1000 cycles at 2000 mA g −1 ) within the operating voltage range of 1.0–4.0 V. The results expand the direct application of MOF for bridging the performance gap between batteries and supercapacitors. Abstract : Hierarchical nanoporous Zr‐MOF (metal−organic framework) has been designed as the anode of hybrid lithium‐ion capacitors (HLICs) with well‐organized porosity for fast Li + ion diffusion and multiple active sites for Li + ion interaction. The HLICs utilizing Zr‐MOF as pseudocapacitive anode and active carbon as cathode exhibit high energy density, large power density, and long‐term cyclability.